2014
DOI: 10.1177/0142723714535875
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and language of mind in narratives: Developmental trends from kindergarten to primary school

Abstract: Narrative competence can be considered an indicator of children's knowledge about other people's minds. The present study investigates the relations between, on the one hand, children's narrative competence and their second order language of mind (comprehension of deception) and, on the other, their developmental trends from kindergarten to primary school. Participants in the study included 142 Italian-speaking children (63 attending their last year in kindergarten and 79 attending first grade in primary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
7
27
0
Order By: Relevance
“…As previous studies on TD children have indicated, from preschool years through middle-childhood, children's narrative skills undergo substantial developments in measures of referential cohesion, narrative structure, global coherence, and the use of connectives (Colozzo & Whitely, 2014;Gamannossi & Pinto, 2014;Mäkinen, Loukusa, Nieminen, Leinonen, & Kunnari, 2014;Peterson & McCabe, 1988). To gain insights into the narrative abilities in Mandarin-speaking children with ASD, therefore, investigations with school-age children should also be the focus for further research.…”
Section: Narrative Coherence In Mandarin-speaking Children With Asdmentioning
confidence: 99%
“…As previous studies on TD children have indicated, from preschool years through middle-childhood, children's narrative skills undergo substantial developments in measures of referential cohesion, narrative structure, global coherence, and the use of connectives (Colozzo & Whitely, 2014;Gamannossi & Pinto, 2014;Mäkinen, Loukusa, Nieminen, Leinonen, & Kunnari, 2014;Peterson & McCabe, 1988). To gain insights into the narrative abilities in Mandarin-speaking children with ASD, therefore, investigations with school-age children should also be the focus for further research.…”
Section: Narrative Coherence In Mandarin-speaking Children With Asdmentioning
confidence: 99%
“…Mental state talk is the set of terms used by people to attribute physiological (e.g., being hungry), perceptual (e.g., see), willing (e.g., desire), emotional (e.g., anger), cognitive (e.g., knowing), moral (e.g., judge), and socio‐relational (e.g., helping) state to others (Bretherton & Beegley, ; Bulgarelli, Testa, & Molina, ; Symons, ). MST is a reliable measure of children's ToM, as demonstrated by the significant correlation with standardized measures of ToM (Accorti Gamannossi & Pinto, ; Peterson & Slaughter, ). Recently, MST has been considered as a stronger measure of ToM than other standardized measures of ToM: it has a higher ecological validity as it can be analysed in children's spontaneous productions; it allows us to explore a wider range of mental states (desires and feelings, besides the cognitive‐related aspects; Hughes, Marks, Ensor, & Lecce, ); and it allows us to analyse ToM development in primary school children, whereas other ToM measures reach a ceiling at the end of kindergarten (Lecce, Cavallini, & Pagnin, ; Wellman & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Narratives represent an ideal context to analyze children’s mental state talk, as through them children develop, practice, and re-describe their ToM (Guajardo and Watson, 2002; Accorti Gamannossi and Pinto, 2014), as is also confirmed by neuro-psychological studies (Marchetti et al, 2015). According to the re-description theory (“representational redescription,” Karmiloff-Smith, 1995), the human mind first develops by learning a process, and then further develops by turning the information that is in the mind into explicit knowledge to the mind.…”
Section: Introductionmentioning
confidence: 83%
“…A few studies have also validated mental state talk by finding significant correlation scores with standardized measures of ToM, such as the false-belief task (Peterson and Slaughter, 2006; Hughes et al, 2011; Accorti Gamannossi and Pinto, 2014). Thus, evidence from the typically and atypically developing population confirm mental state talk as a reliable indicator of children’s understanding of other people’s ToM.…”
Section: Introductionmentioning
confidence: 99%